Acceleration, Deceleration and Dynamic Stress Load in Elite Hurling: A Between-Quarter and Between-Position Comparison - Damien Young; Giuseppe Coratella (MDPI AG, 2021)
This study described the decrement in accelerations, decelerations and dynamic stress load (DSL) between quarters in elite hurling. GPS (10-Hz) were used to record data from 42 players over 22 games (2018-2020 season). The number of accelerations and decelerations and DSL between quarters were assessed. Accelerations and decelerations were greater in Q1 than Q2 (ES = 0.28 and ES = 0.44, respectively), and Q4 (ES = 0.57 and ES = 0.60, respectively), and in Q3 compared to Q4 (ES = 0.50 and ES = 0.44, respectively). The DSL was 56 ± 21 AU in Q1, 56 ± 20 AU in Q2, 52 ± 20 AU in Q3 and 56 ± 24 AU in Q4. There was a decrease in DSL in Q3 compared to Q1 (ES = −0.20) and Q2 (ES = −0.20). Each position experienced a temporal decrease in at least one quarter (ES = 0.43-1.46) in all metrics except full-backs', half-backs' and full forwards' accelerations, midfielders' decelerations and midfielders' and half forwards' DSL. Current data show temporal decrements in running performance in Q2 and Q4 and DSL in Q3. Players should be conditioned to minimize the drop-off in running performances following the third quarter.